Occupational Stress Perception and Healthy Lifestyle in Railroad Workers - Ostan, Iztok; Poljšak, Borut; Podovšovnik Axelsson, Eva (Promet - Traffic&Transportation, 2011)
A survey was performed in 2008 on a representative stratified sample of 245 railroad employees in Slovenia (168 blue-collar and 77 white-collar workers) with the aim of exploring different dimensions of workers’ lifestyle health. For this purpose a special questionnaire was developed. The intensity of perceived job stress was measured with one general index based on a 4-point ordinal scale. There were 54.3% of employees who perceived their work as stressful or very stressful. No significant differences between blue- and white-collar workers were found. Twenty-six dimensions of lifestyle were measured. There were 66.9% of interviewed employees who were found to be overweight or obese (BMI 25 or higher). Differences in lifestyle between blue- and white-collar workers were not significant at the level of 0.05, except for some dimensions: blue-collar workers spend more time in the open air and sunlight and consume lunch as the main meal more regularly. In general, lifestyle was not confirmed as statistically significant (at 0.05 level) moderator of perceived job stress, explaining just 11% of variance. However, there are some dimensions that are significantly (P<0.05) associated with occupational stress: employees that have regular bowel movements, sleep well and evaluate that they do not eat too much perceive their work as less stressful.